Dimensi Sosiologis Sufisme dalam Lintasan Sejarah: dari Asketisme Sufisme-Klasik hingga Post-Modernisme - Nurhayati, Ifa (Program Pascasarjana UIN Sunan Ampel Surabaya, 2008)
Sufism has evolved from time to time and from society to another by presenting itself in various forms and ways. By virtue of its tenets, Sufism has influenced many societies and different cultures. Sufis have played a significant role in their respective societies as religious mentors or else as political advisors. Many of them have otherwise stood in opposition to the political authority and proposed a better way of running the society. Across history, Sufism has shown itself as a dynamic and innovative social and religious force. In the final analysis, Sufism cannot be ignored as the major contributor to the structure of Islamic civilization. In the meantime, the social and religious malaises that we witness in modern time have called Sufism into play. Modernism has produced an unbalanced life, triggering the absolutistic way of life where a man is aware only of his physical dimension and ignoring his spiritual inner being. Here, Sufism can play its important role. The modern intellectual paradigm that puts more emphasis on empiricism and rationalism and produces as a result the positivistic mode of thinking has paved the way for Sufism to occur and recur as the dominant player in the domain of man-personality building. This paper is concerned with this issue and other related problems. Putting in mind that Sufism has its social dimension the paper believes that it has something to offer for modern men living in time of great uncertainty.